Policy Recommendations for Enhancing Employees' Job Performance Based on Structural Equation Model: A Case Study of Commercial Banks in Vietnam - Quoc Huy Nguyen; Phan Thanh Tam (Ianna Journal of Interdisciplinary Studies)
Background: The banking system wants to develop quickly, sustainably, and meet digitalisation requirements, so it needs a team of highly qualified staff. Moreover, employee career competency is one of the most critical issues for organisations, helping them maintain a competitive position in the market.